Systems Pharmacological Approach to Investigate the Mechanism of Hericium erinaceus for Alzheimer's Disease - Gunter P. Eckert; Song Zhen-Yan; Cheng Shao-Wu (KeAi Communications Co., Ltd., 2019)
Objective: To confirm evidence regarding the potential therapeutic effect of Hericium erinaceus (H. erinaceus, Hou Tou Gu, 猴头菇) on Alzheimer's disease (AD) using a system pharmacological approach in silico. Methods: The active compounds of H. erinaceus were screened from the TCMDatabase@Taiwan, PubMed, and Pubchem. The predicted targets of H. erinaceus were selected by using the Similarity Ensemble Approach Database and the DisGeNET database was used to screen the targets related to AD. The compound-target-AD network was built. GO analysis and Pathway enrichment analysis were used for bioinformatics analysis. Results: A total of 21 kinds of H. erinaceus active compounds were screened by network pharmacology, showing 451 predicted targets of active compounds. Among them, 165 targets were associated with AD, and the compounds in H. erinaceus were highly connected to AD-related signaling pathways and biological processes, such as cholinergic synaptic transmission, inflammation-related pathways and neurotrophin signaling pathway. Conclusions: Our results indicate that compounds in H. erinaceus interact with multiple targets in a synergetic way and the anti-inflammatory, anti-apoptosis and synaptic transmission enhancing effects of H. erinaceus might contribute to its major therapeutic effects on Alzheimer's disease. Keywords: Systems pharmacology, Hericium erinaceus (Hou Tou Gu, 猴;头;菇;) Alzheimer's disease, In silico